2019
DOI: 10.1371/journal.pone.0213035
|View full text |Cite
|
Sign up to set email alerts
|

High incidence and prevalence of visual problems after acute stroke: An epidemiology study with implications for service delivery

Abstract: Background Visual problems are an under-reported sequela following stroke. The aim of this study is to report annual incidence and point prevalence of visual problems in an acute adult stroke population and to explore feasibility of early timing of visual assessment. Methods and findings Multi-centre acute stroke unit, prospective, epidemiology study (1 st July 2014 to 30 th June 2015). Orthoptists reviewed all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 23 publications
2
105
0
1
Order By: Relevance
“…They were tested with confrontational testing as a part of NIHSS, which has been proven to underestimate the frequency of stroke‐related VFD . Full visual assessment including perimetry was done at a median of 8 days, which is somewhat earlier than in other comparable studies . With perimetry, the frequency of detected VFD in our study was higher at admittance, 79%.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…They were tested with confrontational testing as a part of NIHSS, which has been proven to underestimate the frequency of stroke‐related VFD . Full visual assessment including perimetry was done at a median of 8 days, which is somewhat earlier than in other comparable studies . With perimetry, the frequency of detected VFD in our study was higher at admittance, 79%.…”
Section: Discussionmentioning
confidence: 63%
“…In our opinion, early identification of visual problems in acute stroke patients would benefit patients, caregivers, and the healthcare system in general. Optimal multidisciplinary structures for this should be established, as also suggested by otherss . Stroke‐related visual field defects are a silent, but serious handicap, easily overlooked by healthcare workers, patients, and surroundings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Stroke-related visual impairment is a well-documented post stroke sequelae with new onset visual impairment affecting about 60% of acute stroke survivors (Rowe et al 2019) Where visual impairment is identified, followup after discharge from hospital stroke units is typically required in outpatient eye clinics. However, many stroke survivors cannot be followed up in hospital for various reasons due to their stroke and/or visual impairments, including transport difficulties, being too unwell and forgetting about appointments due to various additional ongoing outpatient appointments.…”
Section: Introductionmentioning
confidence: 99%